2002
DOI: 10.1177/153537020222700812
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Attenuates Postischemic Depressed Myocardial Function by Increasing Myofilament Ca2+ Sensitivity in Rat Myocardium1

Abstract: The present study investigated whether genistein, a broad-spectrum tyrosine kinase inhibitor, could increase the myofilament Ca2+ sensitivity and partially reverse postischemic depressed myocardial function. Left ventricular papillary muscles were isolated from adult Wistar rats and loaded with the Ca2+ indicator, aequorin. The use of fluorocarbon immersion with hypoxia simulated a model of ischemia. Myofilament responsiveness to Ca2+ was evaluated from force-[Ca2+], relationship recorded during tetani in papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…34 The soy isoflavones have been reported to be responsible for the beneficial effects of soy foods against a number of diseases. [35][36][37] Genistein has also been reported to have various bioactivities, such as a radical-scavenging action, activation of antioxidant enzymes, suppression of oxidative DNA damage, reduction of methyl glyoxal-induced mononuclear cell apoptosis, prevention of LDL oxidation, 38,39 and inhibition of NT formation. 40 Recently, genistein was shown to modulate processes involved in carbohydrate and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The soy isoflavones have been reported to be responsible for the beneficial effects of soy foods against a number of diseases. [35][36][37] Genistein has also been reported to have various bioactivities, such as a radical-scavenging action, activation of antioxidant enzymes, suppression of oxidative DNA damage, reduction of methyl glyoxal-induced mononuclear cell apoptosis, prevention of LDL oxidation, 38,39 and inhibition of NT formation. 40 Recently, genistein was shown to modulate processes involved in carbohydrate and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The soy isoflavones, particularly genistein, have undergone extensive research since their discovery in 1987 34 . The soy isoflavones have been reported to be responsible for the beneficial effects of soy foods against a number of diseases 35–37 . Genistein has also been reported to have various bioactivities, such as a radical‐scavenging action, activation of antioxidant enzymes, suppression of oxidative DNA damage, reduction of methyl glyoxal‐induced mononuclear cell apoptosis, prevention of LDL oxidation, 38,39 and inhibition of NT formation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that GS prevents cardiac hypertrophy induced by isoproterenol in rats 19 and protects against Cardiac toxicity induced by doxorubicin in mice 16 . Furthermore, GS gives an effective reduction of postischemic depressed myocardial function and recovers myofibrillar responsiveness to Ca2+ in rats 20 . In agreement, current study verified that simultaneous administration of GS to rats exposed to CF caused significant reduction in serum levels of troponin I and MDA, indicating GS cardiac protective effect.…”
Section: Discussionmentioning
confidence: 93%
“…In isolated ventricular papillary muscle, contractile function was depressed by hypoxia followed by reoxygenation, and this depression was ameliorated by the isoflavone genistein, which was associated with an improvement of the Ca 2+ responsiveness of the myofilaments [8]. Similarly, in cultured cardiomyocytes, hypoxia reoxygenation-induced cellular damage was attenuated with green tea polyphenols, by virtue of increased cytosolic antioxidant activity and cell viability, and reduced lipid peroxidation [9,10].…”
Section: Cytoprotection Of Cardiomyocytes By Polyphenolsmentioning
confidence: 99%